Gasotransmitters bridging tumor biology and immunity: from pathophysiological insights to therapeutic potential - Ballerini, Giulia; Balboni, Andrea; Garlatti, Valentina; Incerti, Martina; Sica, Antonio; Consonni, Francesca Maria (Frontiers in Immunology, 2026)
The tumor microenvironment (TME) is a highly intricate and dynamic milieu, comprising neoplastic, immune and stromal cells in concert with extracellular matrix components, all engaged in continuous bidirectional crosstalk that critically orchestrates disease progression and therapeutic resistance. Beyond the local context, the TME is deeply shaped also by systemic influences, such as inflammatory mediators, metabolic cues and hematopoietic perturbations, collectively fostering a tumor-permissive macroenvironment. The interplay between local and systemic signals plays a pivotal role in modulating cellular differentiation, immune dynamics and stromal architecture, thereby sustaining malignancy. Among the myriad regulatory modulators involved in this complex network, endogenously produced gasotransmitters, namely carbon monoxide (CO), nitric oxide (NO) and hydrogen sulfide (H2S), have emerged as key modulators of tumor biology. These small, diffusible molecules exert a context-dependent spectrum of both pro-and anti-tumorigenic effects, influenced by their concentration, cellular source and tumor-specific microenvironmental conditions. Through the modulation of redox balance, metabolic signaling and epigenetic regulators, gasotransmitters impact immune cell functions, stromal remodeling and tumor cell behavior, thereby contributing to either immune evasion and therapy resistance or, conversely, to tumor suppression. Despite their growing relevance, the molecular mechanism governing these dualistic roles remain incompletely elucidated. This review provides a comprehensive overview of the current knowledge regarding the roles of CO, NO and H2S in shaping TME. We focus on their influence on immune, stromal and tumor cell differentiation, metabolism and function, and discuss how this understanding could inform novel therapeutic strategies aimed at reprogramming the TME to enhance clinical outcomes in cancer treatment.